Assessment of ZnO and SiO2 nanoparticle permeability through and toxicity to the blood–brain barrier using Evans blue and TEM - Shim KH; Jeong KH; Bae SO; Kang MO; Maeng EH; Choi CS; Kim YR; Hulme J; Lee EK; Kim MK; An SSA (International Journal of Nanomedicine, 2014)
Kyu Hwan Shim,1 Kyeong-Hoon Jeong,2,3 Sun Oh Bae,1 Min O Kang,1 Eun Ho Maeng,4 Cheol Soo Choi,2,3 Yu-Ri Kim,5 John Hulme,1 Eun Kyu Lee,1 Meyoung-Kon Kim,5 Seong Soo A An1 1Department of Bionano Technology, Gachon Medical Research Institute, Gachon University, Seongnam-si, Republic of Korea; 2Korea Mouse Metabolic Phenotyping Center, Lee GilYa Cancer and Diabetes Institute, Gachon University, Incheon, Republic of Korea; 3Division of Endocrinology and Metabolism, Department of Internal Medicine, Gachon University Gil Medical Center, Incheon, Republic of Korea; 4Department of Analysis, Korea Testing and Research Institute (KTR), Gimpo, Republic of Korea; 5Department of Biochemistry and Molecular Biology, Korea University Medical School and College, Seoul, Republic of Korea Abstract: As increasing variants of nanoparticles (NPs) are being used in various products, it has become apparent that size alone can no longer adequately explain the variety of generated toxic profiles. Recent studies with NPs have suggested that various sizes of NPs could determine in vitro toxicity. In an attempt to address concerns regarding neurotoxicity of zinc oxide (ZnO) and silica (SiO2) NPs, these were examined after exposing them via oral, dermal, and intravenous administrations of NPs and their toxicological effects on the brain over a prescribed period of time were assessed. After 28 days of repeated oral administrations of ZnO or SiO2 independently, possibly due to damages to the blood brain barrier (BBB), neurotoxicity, were investigated by Evans blue technique. Next, in order to assess whether ZnO NPs could compromise the BBB, ZnO NPs were intravenously injected on day 0, 7, 14, 21 and 28 no further treatment was administered for 62 days. Deposition of SiO2 in brain from repeated dermal and oral administrations for 90 days were evaluated by transmission electron microscopy coupled with scanning energy-dispersive X-ray spectroscopy. Physiochemical profiles were principally determined on particle size at the beginning of the current toxicity investigations on ZnO and SiO2 NPs. The BBB was found to be intact after independent repeated oral administrations of ZnO or SiO2 NPs for 28 days, suggesting no significant damage. Neuronal death was also not observed after the intravenous administrations of ZnO NPs. After 90 days of repeated dermal and oral administration of SiO2 NPs, no deposition of NPs was observed in hippocampus, striatum, and cerebellum regions using transmission electron microscope analyses. These observations suggest that the BBB was not compromised and was able to block penetration of ZnO and SiO2 NPs, resulting in significant neurotoxic effects. Moreover, absence of SiO2 in three regions of brain after dermal and oral administrations for 90 days suggested that brain was protected from SiO2. No behavior change was observed in all studies, suggesting that 90 days may not be long enough to assess full neurotoxicity of NPs in vivo. Keywords: zinc oxide, silica, BBB, neurotoxicity, penetration, administration